2016
DOI: 10.1186/s12887-016-0708-5
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes in pregnancies resulting from oocyte donation: a cohort study in Sweden

Abstract: BackgroundPregnancies resulting through oocyte donation have been associated with increased risk for adverse outcomes for the mother, such as gestational hypertensive disorders. However, little is known about possible neonatal complications of such pregnancies. The purpose of this study was to evaluate the neonatal health outcomes among singleton pregnancies in a population of relatively young and healthy oocyte recipients in Sweden, taking into account the medical indication leading to treatment.MethodsThis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…Consistent with prior literature, we found an increased risk of IPD and its components in autologous and donor IVF pregnancies when compared to non-IVF pregnancies. 1,14,16,17 For autologous IVF, the majority of IPD was mediated through multifoetal gestations, which was consistent with a prior study. 4 We showed that in donor IVF, 37.5% of the relationship was mediated through multifoetal gestations, meaning that approximately 60% of the relationship between donor IVF and IPD was not explained by the increased incidence of pregnancies with multifoetal gestations.…”
Section: Principal Findingssupporting
confidence: 86%
“…Consistent with prior literature, we found an increased risk of IPD and its components in autologous and donor IVF pregnancies when compared to non-IVF pregnancies. 1,14,16,17 For autologous IVF, the majority of IPD was mediated through multifoetal gestations, which was consistent with a prior study. 4 We showed that in donor IVF, 37.5% of the relationship was mediated through multifoetal gestations, meaning that approximately 60% of the relationship between donor IVF and IPD was not explained by the increased incidence of pregnancies with multifoetal gestations.…”
Section: Principal Findingssupporting
confidence: 86%
“…A recent study from Sweden analyzed the neonatal outcome in births resulting from donor and autologous oocytes with birth defects as one of the outcomes assessed. Though the birth defect rates were similar in these groups in donor oocytes (4/72) and autologous oocytes (4/60; 95% CI 0.20‐0.34), the numbers were too low to be significant . Another study from our group found similar rates of birth defects in pregnancies following fresh ET using autologous (1.39%) vs donor oocytes (1.32%) as a perinatal outcome over a 1‐year period, but again, the number of cases (4 each) were less in each subgroup .…”
Section: Discussionmentioning
confidence: 60%
“…The risks for the mother and the neonate with gamete donation and embryo donation are not fully understood and have not yet been thoroughly investigated. There seems to be a consensus that the risk for women to have pregnancy complications such as preeclampsia and bleeding and the risk for the neonate to be born prematurely or with low birth weight is of considerable importance [ 20 , 21 ]. Having premature and small for gestational children might also affect the mother and family mentally, as well as economically and socially, both in long-term as well as in short-term [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%